Unfolding experimental distortions in beta spectrometry - Craveiro, Gaël; Leblond, Sylvain; Mougeot, Xavier; Vivier, Matthieu (Frontiers in Physics, 2024)
The distortions of measured beta spectra are addressed by means of unfolding algorithms.Two different approaches, the Maximum-Likelihood Expectation-Maximization and the Tikhonov regularization, are tested on various simulated spectra, for which the initial spectrum to retrieve is known, and on a 99 Tc spectrum measured with our dedicated setup. Statistical uncertainties of distorted measured spectra are propagated by determining the covariance matrices. Both algorithms provide satisfactory results but Tikhonov performs overall better for most of the studied radionuclides. Highlight is made on the necessity to employ at least two independent methods to ensure the accuracy of the unfolded spectra and to estimate the internal bias of each algorithm.